Eksekusi Hipotek Kapal Tanpa Putusan Pengadilan: Studi Kasus PT Vs. Perbankan Indonesia - Oktavia, Stevanny; Rahmadani Islami Putri (JURNAL MINUTA, 2026)
The execution of ship mortgage collateral must comply with applicable legal regulations to ensure legal certainty for both creditors and debtors. Ship mortgages are regulated under Law Number 17 of 2008 on Shipping, the Commercial Code, and other relevant regulations. Creditors have the right to execute the mortgaged ship if the debtor defaults, using the Grosse Akta Hipotek, which has the same executorial power as a court ruling. However, in practice, improper executions often occur, such as ship seizures without court authorization. This study examines the proper procedure for executing ship mortgage collateral under legal regulations and the legal protection available for debtors facing unlawful execution. The findings indicate that debtors have the right to retain ownership of the ship and can seek legal remedies in cases of violations. Furthermore, alternative dispute resolution mechanisms, such as mediation or arbitration, can be utilized to avoid prolonged litigation. The government also plays a crucial role in establishing clearer policies on ship mortgage execution to protect the interests of both parties. In conclusion, legal certainty in the execution of ship mortgage collateral can only be achieved through strict adherence to regulations, effective communication between debtors and creditors, and the utilization of available legal mechanisms to prevent misuse in the execution process.